Prognostic and Immune-Infiltrate Significance of miR-222-3p and Its Target Genes in Thyroid Cancer - Zhang, Taofeng; Chen, Yihuan; Lin, Weixun; Zheng, Jiehua; Liu, Yiyuan; Zou, Juan; Cai, Jiehui; Chen, Yaokun; Li, Zhiyang; Chen, Yexi (Frontiers in Genetics, 2021)
Thyroid cancer (THCA) is a common endocrine malignancy. With increasing incidence and low mortality, balancing the therapeutic approach is an inevitable issue. This study aimed to confirm the role of miR-222-3p and its target genes in THCA survival and immune infiltration. From different expression analyses based on the GEO and TCGA databases, we predicted and subsequently identified the key target genes of miR-222-3p. We then explored the expression, enrichment, pairwise correlation, protein expression, survival analysis, principal component analysis, and immune significance of the critical genes using bioinformatics analysis. The present study demonstrated that NEGR1, NTNG1, XPNPEP2, NTNG2, CD109, OPCML, and PRND are critical genes. The miR-222-3p was highly expressed, probably leading to low NEGR1 and high PRND expression in THCA tissues. Low NEGR1 expression indicated favorable prognosis in THCA patients, and high PRND expression indicated poor prognosis. Seven critical genes were significantly related to gender, age, race, tumor stage, and lymph node metastasis. In addition, the seven-gene biomarker exhibited a certain diagnostic value. Finally, CD109 expression was closely correlated with immune cells, especially B cells and CD4+ T cells. The miR-222-3p and its critical target genes could be promising biomarkers for the prognosis of THCA and may emerge as key regulators of immune infiltration in THCA.